2005
DOI: 10.1503/cmaj.050786
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring the severity of depression and remission in primary care: validation of the HAMD-7 scale

Abstract: O ptimal management of major depressive disorders is enhanced by applying a chronic illnessmanagement model with precise and measurable therapeutic endpoints. 1 In contradistinction to several other chronic medical disorders, biological markers of illness activity in depression do not currently exist. In the interim, therapeutic progress is monitored by evaluating changes in the severity of depressive symptoms and in functional domains. This concatenation of findings is particularly disconcerting in view of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 24 publications
1
84
0
Order By: Relevance
“…Nonetheless, reliability results for short versions indicated that that scales has good sensitivity and specifity scores 23 and HAMD was not sensitive to specify depression symptoms as expected 12,13,17 . Addictionally, in contrast to the other subscales the McIntyre et al 8 subscale perform the best reliability and sensibility scores, and was the best version to predict results as HAMD 17, and showed the best correlation indices. So far, MADRS was the unique scale able to differentiate depressive symptoms between groups, showing that at entering time (V0) and after one month after medication (V4) the scale was able to detect and differentiate groups, indicating that MDD group has more symptoms than BD.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Nonetheless, reliability results for short versions indicated that that scales has good sensitivity and specifity scores 23 and HAMD was not sensitive to specify depression symptoms as expected 12,13,17 . Addictionally, in contrast to the other subscales the McIntyre et al 8 subscale perform the best reliability and sensibility scores, and was the best version to predict results as HAMD 17, and showed the best correlation indices. So far, MADRS was the unique scale able to differentiate depressive symptoms between groups, showing that at entering time (V0) and after one month after medication (V4) the scale was able to detect and differentiate groups, indicating that MDD group has more symptoms than BD.…”
Section: Discussionmentioning
confidence: 92%
“…The psychometric properties of HAMD scale has been questioned, and considered as an imprecise scale. This way, tentatives to refine this scale was proposed, using versions based on core symptoms 8,12,13 . In the present study, HAMD 17 scores were reliable and satisfactory, and this could be comparable to Trajković et al 1 study, that related good properties in depression patients (primary diagnosis or with comorbidities) and with Bagby et al 12 revision, that found a Cronbach's Alpha (α > 0.70) and the internal reliability Referring to short versions, satisfactory; however, the 7 item version was the most adequate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a number of clinician-rated and/ or self-rated scales have been widely used in research and are increasingly used in ongoing clinical monitoring of depression (Chung et al 2013;Duffy et al 2008;Katzelnick et al 2011). These include the PHQ-9 (http://www.integration.samhsa.gov/images/res/PHQ%20-%20Questions.pdf; Kroenke et al 2001), the clinician-rated Hamilton Rating Scale for Depression (Ham-D; http://healthnet.umassmed.edu/mhealth/HAMD.pdf; Hamilton 1960;McIntyre et al 2005), and the Inventory of Depressive Symptomatology (IDS), which is available in clinician-rated and self-rated versions (http://www.ids-qids.org/; Rush et al 1996). Other symptom scales are described in Handbook of Psychiatric Measures, 2nd Edition, edited by Rush et al (2008).…”
Section: Methodsmentioning
confidence: 99%